The Power of Heritage and Agricultural Attractions in Driving the Development of Agri-Tage Tourism Destination - Irany Windhyastiti; Umu Khouroh; Sri Wahyu Lelly Hana Setyanti; Syarif Hidayatullah; Abdul Waris; Christina Sri Ratnaningsih (Jurnal Bisnis dan Manajemen, 2025)
This research was conducted in a tourist area that combines agricultural and heritage (agri-tage) tourism.This study aims to: 1) analyze the influence of tourist attractions on the development of tourism destination , 2) analyze the influence tourism support facilities on the development of tourism destination,3) analyze the influence of image and promotion on the development of tourism destination, 4) analyze the influence of the role of government on the development of tourism destination, and 5) analyze the influence of community engagement on the development of tourism destination. Sekaran Hamlet, Sekarpuro Village, Malang Regency offers cultural tourism potential, namely ancient sites (pre-Majapahit sacred buildings) and agricultural panoramas. The population was a rural community, and the sample size was 373 respondents. The data were analyzed using multiple regression. The result show: 1) Tourist attractions have a significant effect on the development of tourism destination, 2) Tourism support facilities don’t have a significant effect on the development of tourism destination,3) Image and promotion have a significant effect on the development of tourism destination, 4) The role of government have a significant effect on the development of tourism destination, and 5) Community engagement on the development of tourism destination. Heritage and agricultural attractions have a dominant influence on tourism development, as most respondents considered the Sekaran Site and its history to be the primary draw for tourists. Furthermore, the natural scenery, including expansive rice fields and agricultural activities, directly accessible to tourists, creates a very different atmosphere from many other tourist destinations that prioritize modern entertainment. These factors offer a more in-depth experience and foster educational aspects and awareness of the importance of sustainability. Supporting tourism facilities are not as influential as cultural and agricultural attractions in the development of tourism destination in Sekarpuro Village. This can be explained because educational tourism based on culture and agriculture prioritizes direct experience and interaction with nature and local culture and does not rely entirely on physical facilities such as parking or restaurants. While adequate facilities are still necessary, the primary appeal of this tourism lies in the educational experiences offered by the Sekaran Site and the surrounding agricultural areas